The The Impact of Service Robots on Employee Burnout in the Hospitality Industry: An Empirical Study - Lukić Nikolić, Jelena; Ostojic, Ivana; Labus, Pero (Industrija, 2026)
Abstract: This study aims to investigate the impact of service robots on the well-being of hospitality employees, with a particular focus on key burnout dimensions: Emotional Exhaustion, Depersonalization, and Personal Accomplishment. Empirical data were collected through an online questionnaire, which was completed by 1,234 employees from the hospitality industry across four Southeastern European countries: Croatia, Serbia, Montenegro, and Bosnia and Herzegovina. The results of the Mann-Whitney U-test revealed significant findings. Employees who worked with service robots reported lower levels of Emotional Exhaustion and Depersonalization compared to those who did not. However, they also experienced lower levels of Personal Accomplishment, suggesting a mixed impact of robot integration on employee well-being. These findings highlight the complex relationship between service robot adoption and employee burnout. While robots may reduce emotional strain and detachment, they may also lead to diminished feelings of professional achievement. The results underscore the importance of adopting a balanced approach to robot integration in hospitality settings, ensuring that technological advancements contribute to both operational efficiency and employee well-being. This research provides valuable insights into the broader implications of service robot use in the hospitality industry.
Keywords: Keywords: service robots, employee burnout, emotional exhaustion, depersonalization, hospitality industry